TMP3-NTRK1 rearranged uterine sarcoma: A case report - William Boyle; Anthony Williams; Sudha Sundar; Jason Yap; Philippe Taniere; Pauline Rehal; Raji Ganesan (Elsevier, 2020)
Introduction: Uterine sarcomas are a group of rare tumours with heterogeneous morphological and genetic features. Recent advances in the molecular characterisation of these tumours have identified a novel clinicopathological category underpinned by NTRK gene fusions. Case report: We present the case of a 42-year-old woman with a polypoid cervical lesion formed of densely cellular, short, haphazard fascicles of monomorphic spindle cells that lacked coagulative necrosis and which showed high mitotic activity. On immunohistochemistry, the tumour was diffusely positive for pan-Trk and weakly positive for CD34 but was negative for a range of other markers, including cytokeratins, smooth muscle markers, hormone receptors and S100. FISH analysis using a NTRK1 break-apart probe was above the threshold for translocation positivity and subsequent next-generation sequencing (NGS) identified a TPM3-NTRK1 fusion. Discussion: NTRK-rearranged uterine sarcomas are a novel subset of gynaecological mesenchymal neoplasms characterised by cytological isomorphism and fibrosarcoma-like morphology. Although distinction from more common mesenchymal neoplasms is possible on the basis of morphology and immunohistochemistry, exclusion of rare differential diagnoses, such as malignant peripheral nerve sheath tumour or the recently described COL1A1-PDGFB fusion sarcoma, requires molecular work-up with FISH or NGS. Identification of these rare tumours is clinically relevant because of their cervical location and the possible role for tropomyosin receptor kinase inhibitors in their treatment.